Light-Driven Plasmonic Color Filters by Overlaying Photoresponsive Liquid Crystals on Gold Annular Aperture Arrays - Liu, Yan Jun; Si, Guang Yuan; Leong, Eunice S. P.; Xiang, Ning; Danner, Aaron J.; Teng, Jing Hua (Advanced materials (Weinheim), 2012)
Light‐driven plasmonic color filters are demonstrated by integrating gold annular aperture arrays with photoresponsive liquid crystals (LCs). Upon photoirradiation, a nematic−isotropic phase transition of the LCs arises from the trans–cis photoisomerization of photochromic LCs. As a consequence, the effective refractive index experienced by the impinging light changes, modulating the transmission intensity.